Impact of chemical composition of the substrate on the synthesis and behaviour of nano hard anodised layers. (1st January 2014) - Hamid, Zeinab Abdel; Abou El-khair, Malak Taher; Gomaa, Mona Hassan; Morsy, Fatma A.; Khalifa, Nevien Abdel Atty
The purpose of this article is to focus on the effect of chemical composition of aluminium substrate on the formation of nano hard anodised aluminium oxide layer (NHAAO) from sulphuric acid bath. The effect of operating conditions (temperature, time and current density) and chemical composition of the substrate on the thickness, pore diameter, morphology, microhardness, abrasion resistance and corrosion resistance of the anodised layers have been investigated. The optimum conditions for the formation of NHAAO films were studied by field emission-scanning electron microscope (FE-SEM) and X-ray photoelectron spectroscopy (XPS). The results demonstrated that the substrate composition, temperature and current density have been effected on the thickness and the pore diameters of the anodic film. XPS analysis illustrated that, the anodised layer consists mainly of oxide. Additionally, the formation of NHAAO on Al or 3004 Al alloy improves the hardness, abrasion resistance and corrosion resistance comparing with unanodised substrates.